Cognition and brain development in children with benign epilepsy with centrotemporal spikes. (4th September 2015) - Garcia‐Ramos, Camille; Jackson, Daren C.; Lin, Jack J.; Dabbs, Kevin; Jones, Jana E.; Hsu, David A.; Stafstrom, Carl E.; Zawadzki, Lucy; Seidenberg, Michael; Prabhakaran, Vivek; Hermann, Bruce P.
Summary Objective Benign epilepsy with centrotemporal spikes (BECTS), the most common focal childhood epilepsy, is associated with subtle abnormalities in cognition and possible developmental alterations in brain structure when compared to healthy participants, as indicated by previous cross‐sectional studies. To examine the natural history of BECTS, we investigated cognition, cortical thickness, and subcortical volumes in children with new/recent onset BECTS and healthy controls (HC). Methods Participants were 8–15 years of age, including 24 children with new‐onset BECTS and 41 age‐ and gender‐matched HC. At baseline and 2 years later, all participants completed a cognitive assessment, and a subset (13 BECTS, 24 HC) underwent T1 volumetric magnetic resonance imaging (MRI) scans focusing on cortical thickness and subcortical volumes. Results Baseline cognitive abnormalities associated with BECTS (object naming, verbal learning, arithmetic computation, and psychomotor speed/dexterity) persisted over 2 years, with the rate of cognitive development paralleling that of HC. Baseline neuroimaging revealed thinner cortex in BECTS compared to controls in frontal, temporal, and occipital regions. Longitudinally, HC showed widespread cortical thinning in both hemispheres, whereas BECTS participants showed sparse regions of both cortical thinning and thickening. Analyses of subcortical volumes showed larger left and right putamens persisting over 2 years in BECTS compared to HC. Significance Cognitive and structural brain abnormalities associated with BECTS are present at onset and persist (cognition) and/or evolve (brain structure) over time. Atypical maturation of cortical thickness antecedent to BECTS onset results in early identified abnormalities that continue to develop abnormally over time. However, compared to anatomic development, cognition appears more resistant to further change over time.